Assessing Levels and Correlates of Implementation of Evidence-Based Approaches for Colorectal Cancer Screening: A Cross-Sectional Study With Federally Qualified Health Centers. (December 2018) - Walker, Timothy J.; Risendal, Betsy; Kegler, Michelle C.; Friedman, Daniela B.; Weiner, Bryan J.; Williams, Rebecca S.; Tu, Shin-Ping; Fernandez, Maria E.
Multiple evidence-based approaches (EBAs) exist to improve colorectal cancer screening in health clinics. The success of these approaches is tied to effective implementation. Therefore, the purpose of this study was to assess the implementation of EBAs for colorectal cancer screening and clinic-level correlates of implementation in federally qualified health centers (FQHCs). We conducted descriptive and cross-sectional analyses using data collected from FQHC clinics across seven states ( n = 51). A clinic representative completed electronic surveys about clinic characteristics (e.g., size, patient characteristics, and medical record system characteristics) and the implementation of Community Guide recommended EBAs (e.g., client reminders, small media, and provider assessment and feedback). We used bivariate Spearman correlations to assess clinic-level correlates with implementation outcomes. Most clinics were planning to implement, in the early implementation stages, or inconsistently implementing EBAs. No EBA was fully implemented by more than nine (17.6%) clinics. Clinic size variables were inversely related to implementation levels of one-on-one education; medical record variables were directly related to implementation levels of client and provider reminders as well as provider assessment and feedback; and rapid and timely feedback from clinic leaders was directly associated with implementation levels of four out of six EBAs. Given the varying levels of implementation, clinics need to assess current use of implementation strategies and improve effective program delivery to increase colorectal cancer screening among their patients. In addition, clinics should also consider how their characteristics may support or serve as a barrier to implementation in their respective settings.